Decision Support Tools (DST) - application in policy, planning and implementation - Trautman, Sabrina; Cramer, Laura K.; Rosenstock, Todd S.; Nowak, Andreea C.; Gosling, Amanda; Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
These training slides, form part of the training delivered to the Africa Group of Negotiators Expert Support Group (AGNES) Climate Leadership Programme. The materials explore the impacts of decision making and introduce the key concepts as well as an overview of decision support tools and the basics of data visualisation. The training delves into the importance of user testing and accessing decision support tools and how critical evidence is for police processes, as explained through the example of climate-smart agriculture investment plans.